The Effects of Ibuprofen and Indomethacin on Human Chronic Myelocytic Leukemia K562 Cell Line: An In-Vitro Study - Afsaneh Bapiri; Mehdi Mohammadzadeh (مجله دانشکده پزشکی اصفهان, 2015)
Background: The amount of COX-2 increases in most cancers due to synthesis of prostaglandins. Therefore, COX-2 inhibitors may play an effective role in cancer therapy. The goal of this study was to investigate the effect of ibuprofen and indomethacin, as anti-inflammatory drugs, on the K562 cell growth and proliferation.